The effect of omega-3 fatty acid supplementation and aerobic exercise on the depression of obese women - Shokofe Yari; Morteza Taheri; Khadijeh Irandoust (فصلنامه ابن سینا, 2018)
Background: Depression is one of the damaging aspects of obesity which has made more aware of the need for prevention and treatment among researchers and officials. In this regard, the purpose of this study was to evaluate the effect of eight weeks of omega-3 supplementation and aerobic exercise on depression in obese women. Materials and methods: In this study, which was performed in Kermanshah city, among obese women 37 subjects, 25-40 years old, with mild to moderate depression were selected and randomly assigned to four groups of aerobic training + supplementation of omega-3, omega-3 supplementation, aerobic training, and control. The aerobic exercise program was performed for eight weeks, three sessions a week, for 30-45 minutes, and an intensity of 65-70% of maximum heart rate. The daily intake of omega-3 supplementation was 2,000 milligrams. Also, Beck Depression Inventory was completed by participants to measure depression before and after the eight weeks. Results: In all three experimental groups, depression showed a significant improvement (p≤0.05). The aerobic group and the aerobic + supplement group showed a significant improvement compared to the supplementary group in terms of depression (p≤0.05). Conclusion: It seems a combination of omega-3 fatty acid supplementation and aerobic exercise can help to improvement the depression of obese women and also it can be used with other exercise programs.